Topical Medication Therapy for Glaucoma and Ocular Hypertension - Wang, Tao; Cao, Linlin; Jiang, Qikun; Zhang, Tianhong (Frontiers in Pharmacology, 2021)
Glaucoma is one of the most common causes of blindness, thus seriously affecting people's health and quality of life. The topical medical therapy is as the first line treatment in the management of glaucoma since it is inexpensive, convenient, effective, and safe. This review summarizes and compares extensive clinical trials on the topical medications for the treatment of glaucoma, including topical monotherapy agents, topical fixed-combination agents, topical non-fixed combination agents, and their composition, mechanism of action, efficacy and adverse effects, which will provide reference for optimal choice of clinical medication. Fixed-combination therapeutics offer greater efficacy, reliable security, clinical compliance and tolerance than non-fixed combination agents and monotherapy agents, which will become a prefer option for the treatment of glaucoma. Meanwhile, we also discuss new trends in the field of new fixed combinations of medications, which may better control IOP and treat glaucoma.